La verdad es que no queremos aprender quechua - Oyola García, Alfredo Enrique (2016)
Mr. Editor: Teaching and learning communication in a different foreign language our mother tongue today are a social necessity and a priority that can be -among others- staff, academic, scientific, professional and cultural (1). Consequently, its use does not depend on the level of mastery of them, but the valuation assigned (2). For example, it would be absurd to think that a health professional may work in a hospital in Germany without mastering German. In this case it becomes a necessity for work, ie, a pre-requisite.